Utilization of palm kernel by-product in bioconversion of black soldier fly larvae: a systematic literature review - Nurul Syafiqah Noor Idzam; Ahmad Razali Ishak; Nazri Che Dom; Norhisham Haron; Emida Mohamed; Mohd Salleh Rofiee; Asmah Awal; Pui, Wee Hua (Pusat Sistematik Serangga ,UKM, 2025)
Palm kernel by-product (PKB) refers to the waste material, mainly solid and fibrous, that remains after the oil has been extracted from the palm fruit kernels. The utilization of PKB in various applications, including bioconversion using Black Soldier Fly (BSF) larvae has promoted sustainable waste management and resource recovery. Many researchers have begun investigating PKB potential in bioconversion, exploring methods to modify its nutritional composition and assess the bioconversion results. Therefore, this systematic literature review seeks to comprehensively evaluate the potential of PKB in BSF larvae bioconversion, emphasizing its influence on BSF larvae growth performance and providing an in-depth characterization of the biomass. The Reporting Standard for Systematic Evidence Syntheses (ROSES) framework was employed in this study. The search strategy was developed by identifying key terms derived from the research question and objective resulting in 11 articles published between 2004 and 2024 being systematically reviewed. The findings specify that PKB can be utilized in unmodified and modified forms, with modifications through mixing with other substrates as well as fermentation. Although PKB can be utilized as a substrate for BSF larvae in its unmodified form, researchers have found that modifying the substrate can significantly enhance its nutritional value as well as improve the growth performance of BSF larvae and its biomass. This review indicates that the modified form of PKB holds substantial potential as a feed source for BSF larvae, facilitating the transformation of PKB into nutrient-rich larvae biomass that is high in protein or lipids.